Faktor-Faktor Yang Memengaruhi Ekspor Neto Bahan Bakar Minyak Di Indonesia Periode 1991-2012 - Reditya Marciawan, I G N Deva Arya; Darsana, Ida Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Since a long time ago, Indonesia known as a country whose rich in natural resources and minerals. But now there are so many problems appear in the oil and gas industry sector, which is quite disturbing Indonesian economic. Import of oil product who continuously increases and cannot be avoided is like proving that the product is becoming one of the staples in Indonesian consumption because of the industrial sector and transportation. The purpose of this study is to analyze the impact of dollar exchange rate, oil prices, consumption per capita, and Gross Domestic Product (GDP) simultaneously and partially to the Indonesia’s fuel net exports. Furthermore, this study also determines which variables have the most dominant influence to Indonesia’s fuel net exports on 1991-2012. The result shows that dollar exchange rate, oil prices, consumption per capita and GDP simultaneously have significant impact to Indonesia’s fuel net exports on 1991-2012. Partially, dollar exchange rate and consumption per capita have negative and significant impact to Indonesia’s fuel net exports on 1991-2012. Meanwhile, GDP partially has not impact to Indonesia’s fuel net exports on 1991-2012. Oil prices have the most dominant impact to the Indonesia’s fuel net exports on 1991-2012.
Keywords: fuel net export; dollar exchange rate; world oil price; consumption per capita; gross domestic product